Maternal attitude and child interest in various play activities before and after mother-child play sessions - Soedjatmiko Soedjatmiko; Hartono Gunardi; Rini Sekartini; Bernie Endyarni Medise; Ikhsan Johnson; Yulianti Wibowo; Ray Wagiu Basrowi (Paediatrica Indonesiana, 2017)
Background Play stimulates children's growth and development. When mothers and their children play, a positive attitude from the mother and adequate interest from the child is required. Little is known about the play activities that effectively stimulate such positive maternal attitude and child interest. Objective To assess for associations between various play activities with maternal attitude and child interest before and after mother-child play sessions. Methods Pre-post intervention questionnaires were distributed to mothers before and after playing with their children. Children were aged 1-5 years, from two play sites (in Surabaya and Makassar), and included using purposive sampling. Eight types of toys/play activities were provided. The allocated time for answering the 17-question survey was 15 minutes. Average scores before and after the mother-child play sessions were analyzed using paired T-test. Results We collected 264 valid questionnaires, 235 in Surabaya and 29 in Makassar. Improvement of maternal attitude after the mother-child play session was found in 132 mothers [mean diff. 0.07 (SD 0.42); 95%CI -0.117 to -0.015; P=0.011]. Play activities with significant improvements in maternal attitude were jigsaw puzzle [mean diff. 0.09 (SD 0.66); 95% CI 0.007 to 0.167;P= 0.033), Lego blocks (mean diff.-0.10 (SD 0.69); 95%CI -0.186 to -0.018; P=0.017), mini-gardening (mean diff. -0.15 (SD 0.75); 95%CI -0.238 to -0.057; P=0.002), sandbox [mean diff.-0.24 (SD 0.83); 95%CI -0.339 to – 0.138; P < 0.001], fishing [mean diff. -0.17 (SD 0.68); 95%CI -0.253 to -0.088; P < 0.001], and animal figurines [mean diff. -0.21 (SD 0.75); 95%CI -0.3 to -0.117;P <0.001]. Improvement of child interest was found in 161 children [mean diff. 0.20 (SD 0.52); 95%CI -0.264 to -0.116; P<0.001]. Play activities with significant improvements in child interest were jigsaw puzzle, Lego blocks, origami, mini-gardening, fishing, and animal figurines. Conclusion Some mother-child play activities, but not all, significantly improve both maternal attitude and child interest toward play.